Snakeroot - Cremer, Andrea R. (Cremer, Andrea R. Nightshade series ;, 2013)
Bosque Mar haunts Adne and Logan's dreams, trying to turn Adne to the dark side as he attempts to escape the Nether, where Calla, Shay and the other Guardians trapped him in the final battle of the War of All Against All.